Transverse Distraction of Great Toe to Enlarge the Donor Site before Finger Reconstruction - Liwen Hao; Kai Rong; Chao Chen; Zhidian Hou; Yaxing Wang; Xu Tian; Zengtao Wang (Orthopaedic Surgery)
Partial great toe transfer is widely used in finger reconstruction. Although satisfactory results have been reported at the recipient's hand, the donor foot still presents with many problems due to the large amount of tissues harvested. In this study, the Ilizarov technique was utilized to enlarge the great toe in order to minimize the amount of tissue sacrificed of the donor foot. In this retrospective study, 23 patients (30 toes) underwent transverse distraction of the great toe for finger reconstruction from September 2020 to December 2022. The width of the contralateral normal finger was set as the objective width gained of distraction. At the last follow‐up, the changes of bone, toenail, plantar skin, vessel, and nerve of the great toe were measured, and postoperative complications were assessed. The time for active distraction was 46.1 ± 8.3 days, with a widening rate of 0.41 ± 0.08 mm/day. Counting in the time for latency and consolidation, the time of treatment with external fixation was 84 ± 11.9 days. At the last follow‐up, the average width of the distal phalanx of the great toe increased from 13.1 to 28.1 mm (p < 0.001). The width of the toenail increased from 15.8 to 30.3 mm (p < 0.001), and the width of the plantar pulp increased from 25.6 to 38.8 mm (p < 0.001). Computed tomography angiography (CTA) and Doppler ultrasound confirmed that the digital arteries and nerves of the great toe were intact after distraction surgery. Two patients needed revision surgery due to complications of pin loosening or premature consolidation. With the help of the Ilizarov technique, the great toe is effectively enlarged after transverse distraction. Multiple tissues of the great toe, including bone, nail, and plantar skin, are regenerated, and more tissues were preserved after toe‐to‐hand transfer. To the best of our knowledge, this is a novel method to enlarge the donor site for finger reconstruction.